THE EFFECT OF LEARNING MOTIVATION AND WORDWALL MEDIA TOWARDS VOCABULARY ENHANCEMENT IN EFL LEARNERS - Devi Nurhayati; Lili Sururi Asipi; Virga Putra Darma (NextGen Education Review Journal, 2025)
This study investigates the effect of learning motivation and the use of WordWall media on vocabulary enhancement among EFL learners. Conducted at SMPN 2 Jatiwangi and SMPN 2 Dawuan, the research involved 224 students who had experience using WordWall in English lessons. Employing a quantitative method with a survey design, data were collected through questionnaires and vocabulary tests. The coefficient of determination (R²) shows a value of 0.648, indicating that 64.8% of students’ vocabulary enhancement can be explained by the combined influence of learning motivation and WordWall media. The remaining 35.2% is influenced by other factors not covered in this study. These results suggest that while digital media like WordWall plays an important role in engaging students, intrinsic factors such as motivation remain the dominant contributor to vocabulary development. This highlights the importance of integrating psychological and technological aspects in EFL learning to foster more effective outcomes.